Centrifugal step emulsification applied for absolute quantification of nucleic acids by digital droplet RPA1. Issue 13 (7th July 2015) - Schuler, Friedrich; Schwemmer, Frank; Trotter, Martin; Wadle, Simon; Zengerle, Roland; von Stetten, Felix; Paust, Nils
<x xml:space="preserve">Abstract</x> Centrifugal step emulsification enables dead volume free emulsification, it was applied to the first digital droplet recombinase polymerase amplification (RPA).